Pemikiran Pendidikan Islam yang Membebaskan - Yusuf Hasan Baharudin (Postgraduate State Islamic Institute (IAIN) Metro, 2021)
Education is the most effective means to liberate and liberate humans from all forms of exploitation and dehumanization. Education should be open to renewal and dialogue. However, until now the reality is that there are still many educational processes that are monological in nature. As a result, human nature or basic potential possessed by students cannot grow and develop following expectations because the process of student growth and development essentially needs to have a humanizing process in the world of education. This concept of education is known as liberating education, namely education that places a communicative or dialogical atmosphere so that an educational atmosphere that is more alive and human will be created. Liberating learning can be optimal if teachers and students can jointly create conducive learning conditions, teachers and students feel free or independent from the crush of expressing their conscience, feelings and ideology. Liberating Islamic education is an educational process that upholds human nature and places a dialogical, communicative atmosphere to create a more lively and humane atmosphere.